PENINGKATAN LITERASI KEUANGAN DAN PEMASARAN DIGITAL BAGI UMKM DI JAKARTA TIMUR - Umi Widyastuti; Osly Usman; Terrylina A. Monoarfa; Shandy Aditya; Diena Noviarini; Meta Bara Berutu (Indonesian Collaboration Journal of Community Services, 2022)
MSMEs are one of the pillars that support the national economy, therefore the government pays great attention to the sustainability of MSMEs. MSME actors in the East Jakarta Sub-Department of MSMEs, Cooperatives and Trade are facing problems regarding the limitations of financial literacy and digital marketing in managing their businesses. One way that can be done to support the success of MSMEs is to provide training on financial records with SIAPIK which is based on a single record. In addition, they were also given directions on digital marketing in an effort to increase sales turnover for MSMEs in the region